2017
DOI: 10.1038/ni.3854
|View full text |Cite|
|
Sign up to set email alerts
|

Cytotoxic and regulatory roles of mucosal-associated invariant T cells in type 1 diabetes

Abstract: Type 1 diabetes is an autoimmune disease resulting from the destruction of pancreatic-beta cells by the immune system involving innate and adaptive immune cells. Mucosal-associated invariant T (MAIT) cells are innate-like T-cells recognizing bacterial riboflavin-precursor derivatives presented by the MHC-I related molecule, MR1. Since T1D is associated with gut microbiota modification, we investigated MAIT cells in this pathology. In T1D patients and non-obese diabetic mice, we detected MAIT cell alterations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
213
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(224 citation statements)
references
References 63 publications
9
213
1
1
Order By: Relevance
“…The in vivo significance of MAIT cell‐mediated cytotoxicity may not be limited to infectious diseases and cancer. In fact, this function has been recently linked to autoimmune diabetes . While autoimmunity is beyond the scope of this review, it is worth mentioning that the cytolytic profile and function of human MAIT cells were implicated in the pathogenesis and severity of type 1 diabetes.…”
Section: Outstanding Questions and Concluding Remarksmentioning
confidence: 99%
“…The in vivo significance of MAIT cell‐mediated cytotoxicity may not be limited to infectious diseases and cancer. In fact, this function has been recently linked to autoimmune diabetes . While autoimmunity is beyond the scope of this review, it is worth mentioning that the cytolytic profile and function of human MAIT cells were implicated in the pathogenesis and severity of type 1 diabetes.…”
Section: Outstanding Questions and Concluding Remarksmentioning
confidence: 99%
“…The discovery of 5‐OP‐RU and 5‐OE‐RU as very potent Ags and the development of MR1‐tetramers, now available from the National Institutes of Health, USA, have opened up the field to start elucidating the roles of MAIT cells in anti‐microbial immunity, in sensing of metabolic changes such as in cancer, stress and cell damage, as well as in immunopathology . The tetramers have also allowed further characterization of the phenotypic identity of MAIT cells and their development, with individual‐ and age‐specific differences now being investigated .…”
Section: Discovery Of Mr1 Bound Antigens That Activate Mait Cellsmentioning
confidence: 99%
“…MAIT cells have the capacity to directly respond to bacterial and fungal pathogens and are located to selectively protect mucosal barriers . In addition, MAIT cells have been implicated in diseases such as asthma and type 1 diabetes . Recently, it has been suggested that MAIT cells confer partial protection from Graft‐ versus ‐Host‐Disease after bone marrow transplantation …”
Section: Introductionmentioning
confidence: 99%